Efficiency of extrinsic and intrinsic charge-carrier photogeneration processes obtained from the steady-state photocurrent action spectra of poly(p-phenylene vinylene) derivatives - Cazati, T.; Santos, L. F. [UNESP]; Reis, F. T.; Faria, R. M. (Springer, 2012)
The efficiency of the charge-carrier photogeneration processes in poly(2,5-bis(3',7'-dimethyl-octyloxy)-1,4-phenylene vinylene) (OC(1)OC10-PPV) has been analyzed by the spectral response of the photocurrent of devices in ITO/polymer/Al structures. The symbatic response of the photocurrent action spectra of the OC1OC10-PPV devices, obtained for light-excitation through the ITO electrode and for forward bias, has been fitted using a phenomenological model which considers that the predominant transport mechanism under external applied electric field is the drift of photogenerated charge-carriers, neglecting charge-carrier diffusion. The proposed model takes into account that charge-carrier photogeneration occurs via intermediate stages of bounded pairs (excitonic states), followed by dissociation processes. Such processes result in two different contributions to the photoconductivity: The first one, associated to direct creation of unbound polaron pairs due to intrinsic photoionization; and the second one is associated to secondary processes like extrinsic photoinjection at the metallic electrodes. The results obtained from the model have shown that the intrinsic component of the photoconductivity at higher excitation energies has a considerably higher efficiency than the extrinsic one, suggesting a dependence on the photon energy for the efficiency of the photogeneration process.